Identification of egg protein-derived peptides as xanthine oxidase inhibitors: virtual hydrolysis, molecular docking, and in vitro activity evaluation - Zhipeng Yu; Yaxin Cao; Ruotong Kan; Huizhuo Ji; Wenzhu Zhao; Sijia Wu; Jingbo Liu; David Shiuan (Food Science and Human Wellness)
The purpose of this study was to screen the xanthine oxidase (XO) inhibitory peptides from egg white proteins through virtual hydrolysis, in vitro activity validation, and molecular docking. The results demonstrated that tripeptide EEK from ovalbumin exhibited potent XO inhibitory activity with an IC50 value of 141 µmol/L. The molecular docking results showed that tripeptide EEK bound with the active center of XO via 3 carbon hydrogen bond interactions, 2 salt bridges, 5 conventional hydrogen bond interactions, and 4 attractive charge interactions. The residues Glu802, Phe1009, and Arg880 may play key roles in the XO catalytic reaction. Especially, the key intermolecular forces of inhibiting XO activity may be special type of hydrogen bonds including carbon hydrogen bond interactions and attraction charge interactions. The novel tripeptide EEK is potential candidates for controlling hyperuricemia.